Kajian Selektivitas Erosi Pada Lahan Budidaya Padi Gogo Di Desa Lau Damak Kecamatan Bahorok Kabupaten Langkat - Rika Tamika; Abdul Rauf; Purba Marpaung (Jurnal Agroekoteknologi, 2015)
Gogo rice as one of many commodities developed on sloping topography, thus potentially increasing run off a water and soil erosion that will transport nutrients to the other place. The aim of the research was to know the Erosion Selectivity on Land Cultivation of Gogo Rice in Countryside of Lau Damak Distric of Bahorok Sub-Province Langkat. The research was conducted from September until November 2014 through 2 stages of activity, it was fieldwork and laboratory activities. The Stages of fieldwork has done in village at Lau Damak District of Bahorok Langkat on 15% slope. The results of field activities was analysis in agriculture faculty laboratory,University of North Sumatra, Medan. The reseach use a t-test to differentiate the nutrients at upper, center, and bottom of the slope. The selectivity of erosion can be seen from the changes in the levels of clay and organic Carbon in the upper, middle and lower slopes. Selectivity erosion can also be seen from the changes, total-N, available P, pH, K, CEC, and soil texture on the part of the slope.The results showed that the Organic Carbon and Total-Nitrogen were significantly differenton the slopes position.Key words : Soil Erosion, selectivity erosion, gogo rice